Self-depart from the Topic ‘Expatriation’ - Mahdi, Ali Talib (International Journal of Psychosocial Rehabilitation, 2020)
Expatriation is a socio-psychological phenomenon that has captured the interest of people and scientists who focus on its nature, causes, motives as well as effects. It is considered a human existential phenomenon inseparable from human existence; therefore, it has become a serious issue tackled in many fields like psychology, Literature, Social analysis and theology. In this study, the researcher has brought to light this phenomenon exploring it from various aspects. Thus, the researcher has examined this phenomenon in Ibn Al- Ambary as a model revealing its different aspects, particularly, the feeling of fear, anxiety and the duality of pessimism and nostalgia that clearly appear in his poems ; and urges him to communicate with wild animals making them his friend instead of people . So these animals become his escape with which he can forget his worries and the deadly feeling of expatriation. Consequently, the researcher has come up with the fact that expatriation can be the result of harsh circumstances that take the person away from his normal sate and deprive him from being secure and happy like exactly what happened to this poet, Ibn Al-Ambary.